REALITA TAGHYIR AL-JINS DAN HUKUM PERKAWINANNYA DALAM PERSPEKTIF ISLAM DI INDONESIA - Fathonah Fathonah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2015)
Marriage, often only associated with the needs of an individual or a private matter for the bride and groom. Therefore there are times when a person is married without being based on religious teachings and the main one they are can happy. Whereas,, legitimate and holy marriage is a social purposes and is land of worship to Allah swt. The marriage in Islam is to unite the pair of the opposite kind, male and female. Now in the modern era there was a transgender marriage (taghyir al-jins), individuals who have committed sex-change operation. In the legislation of marriage in Indonesia says that the pillars of marriage should be there the bride and groom of men and women, also presuppose both of them must be ta'yin (clear their existence and sex). While the transgender marriage is a some one (male / female) married to someone who had experienced taghyir al-jins (who swapped sex become the vagina or penis). This paper examines how the law of taghyir al-jins, what factors trigger genital surgery, and how the marriage law for them in Indonesia Islamic perspective.